Electroactive shape memory polyurethane composites reinforced with octadecyl isocyanate-functionalized multi-walled carbon nanotubes - Sun, Yadong; Teng, Jiachi; Kuang, Yi; Yang, Shengxiang; Yang, Jiquan; Mao, Hongli; Gu, Zhongwei (Frontiers in Bioengineering and Biotechnology, 2022)
Shape memory polymers (SMPs) have a wide range of potential applications in many fields. In particular, electrically driven SMPs have attracted increasing attention due to their unique electrical deformation behaviors. Carbon nanotubes (CNTs) are often used as SMP conductive fillers because of their excellent electrical conductivities. However, raw CNTs do not disperse into the polymer matrix well. This strictly limits their use. In this study, to improve their dispersion performance characteristics in the polymer matrix, hydroxylated multi-walled carbon nanotubes (MWCNT-OHs) were functionalized with octadecyl isocyanate (i-MWCNTs). Polyurethane with shape memory properties (SMPU) was synthesized using polycaprolactone diol (PCL-diol), hexamethylene diisocyanate (HDI), and 1,4-butanediol (BDO) at a 1:5:4 ratio. Then, electroactive shape memory composites were developed by blending SMPU with i-MWCNTs to produce SMPU/i-MWCNTs. The functionalized i-MWCNTs exhibited better dispersibility characteristics in organic solvents and SMPU composites than the MWCNT-OHs. The addition of i-MWCNTs reduced the crystallinity of SMPU without affecting the original chemical structure. In addition, the hydrogen bond index and melting temperature of the SMPU soft segment decreased significantly, and the thermal decomposition temperatures of the composites increased. The SMPU/i-MWCNT composites exhibited conductivity when the i-MWCNT content was 0.5 wt%. This conductivity increased with the i-MWCNT content. In addition, when the i-MWCNT content exceeded 1 wt%, the composite temperature could increase beyond 60 °C within 140 s and the temporary structure could be restored to its initial state within 120 s using a voltage of 30 eV. Therefore, the functionalized CNTs exhibit excellent potential for use in the development of electroactive shape memory composites, which may be used in flexible electronics and other fields.